2016
DOI: 10.1111/jan.13148
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of patient preference and adherence to the correct use of graduated compression stockings to prevent deep vein thrombosis in surgical patients

Abstract: Patient adherence was generally higher with knee length than thigh length stockings. However, the studies reflect patient adherence in a hospital setting only, where patients are observed by healthcare professionals; it is likely that adherence reduces once patients have been discharged from hospital. Patients preferred knee length stockings over thigh length stockings. In many clinical settings, any difference in efficacy between thigh length and knee length stockings may be rendered irrelevant by patient pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 20 publications
0
22
0
2
Order By: Relevance
“…The same study found similar results with the length of AES and this was also found in a review of adherence in surgical specialities. 46 There is, therefore, scope for further research using a randomised control study design to assess widely used IPC machines, the length of sleeves and the effect both factors have on adherence, particularly in relation to comfort.…”
Section: Discussionmentioning
confidence: 99%
“…The same study found similar results with the length of AES and this was also found in a review of adherence in surgical specialities. 46 There is, therefore, scope for further research using a randomised control study design to assess widely used IPC machines, the length of sleeves and the effect both factors have on adherence, particularly in relation to comfort.…”
Section: Discussionmentioning
confidence: 99%
“…; Wade et al. ) and are particularly difficult to put on and take off (Johnson ; Anand et al. ), resulting in poor adherence(Anand et al.…”
Section: Introductionmentioning
confidence: 99%
“…The patients should constantly focus on whether the elastic stockings are worn correctly, because the actual pressure value is closely related to the correct wearing. In further, according to the guideline of health promotion in UK national institute, the patients should start to use elastic stockings until they have complete activity ability [ 5 , 17 , 33 ]. On the other hand, IPCD is a engineering device that can provide progressive pressure on the ankle, calf, and thigh.…”
Section: Discussionmentioning
confidence: 99%
“…The common physical measures include IPCD, gradient elastic stockings, plantar vein pumps, etc. Currently, they can be used alone or as an auxiliary measure for drug prevention, and are an important strategies for DVT prevention [ 17 ]. Specifically, IPCD can be considered as one common mechanical precaution for DVT in clinical practice [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%